The Legal Position of Indonesian in Foreign Business Contracts - Maulana, Riski; Lubis, Tiva Novianti (Jurnal Konstatering, 2024)
This research evaluates the legal status of the Indonesian language in foreign business contracts in Indonesia, considering its crucial role in the validity and enforceability of agreements in the current era of globalization. Using a normative juridical approach and case studies, this study found that despite the legal obligation, the implementation of using the Indonesian language is often hindered by the understanding of foreign parties, which can lead to legal disputes. Therefore, clear guidelines and intensive socialization efforts are needed to ensure compliance with these regulations, in order to support more effective legal policies and practices in the field of international business.